Performance of ‘Salustiana’ sweet orange on different rootstocks under Brazilian subtropical conditions - de Carvalho, Deived Uilian; Neves, Carmen Silvia Vieira Janeiro; da Cruz, Maria Aparecida; Colombo, Ronan Carlos; Yada, Inês Fumiko Ubukata; Leite Junior, Rui Pereira; Tazima, Zuleide Hissano (Scientia horticulturae, 2021)
•‘Swingle’ citrumelo and ‘C-13’ citrange enhanced ‘Salustiana’ sweet orange yield.•Fruit from all rootstocks exhibited acceptable physicochemical traits.•‘Rangpur’ lime did not promote substantial growth of ‘Salustiana’ sweet orange trees.•‘Salustiana’ sweet orange may be a profitable option for diversifying citrus production in Southern Brazil. Rootstocks play an important role in the agronomic performance of the citrus tree. Due to intense disease pressure in most citrus growing regions, particularly the humid subtropics, grove diversification by increasing rootstock genetic diversity can promote resilience. We evaluated the performance of ‘Salustiana’ sweet orange grafted on five different rootstocks over ten cropping seasons (2008–2017) under the subtropical edaphoclimatic conditions of State of Paraná, Southern Brazil. The experiment was a randomized block design with six replicates of the rootstocks ‘Rangpur’ lime, ‘Cleopatra’ mandarin, ‘Sunki’ mandarin, ‘Swingle’ citrumelo, and ‘C-13’ citrange. ‘Salustiana’ scions were assessed for vegetative growth, fruit quality, and yield. Further, rootstock stability was also analyzed, and new grove planting density and yield estimated. ‘Rangpur’ lime is the most frequently planted rootstock in Brazil, however it significantly reduced overall tree size of ‘Salustiana’ compared to all other rootstocks. Trees on all five rootstocks produced fruits with physicochemical properties that meet the requirements for both the fresh market and the juice processing industry. ‘Salustiana’ scions on ‘C-13’ and ‘Swingle’ produced the highest cumulative yields and they were twice as productive as the ones on ‘Rangpur’. Rootstock clearly impacts yield estimation indices for ‘Salustiana’ trees. Tree performance is enhanced when grafted on ‘C-13’ citrange and ‘Swingle’ citrumelo, reaching good stability across ten years of fruit yield. Both of these rootstocks have great potential for application in new citrus plantings in Southern Brazil.